2021
DOI: 10.1016/j.devcel.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

ORF3a of SARS-CoV-2 promotes lysosomal exocytosis-mediated viral egress

Abstract: Viral entry and egress are important determinants of virus infectivity and pathogenicity. β-Coronaviruses, including the COVID-19 virus SARS-CoV-2 and MHV, exploit the lysosomal exocytosis pathway for egress. Here we show that SARS-CoV-2 ORF3a, but not SARS-CoV ORF3a, promotes lysosomal exocytosis. SARS-CoV-2 ORF3a facilitates lysosomal targeting of the BORC-ARL8b complex, which mediates trafficking of lysosomes to the vicinity of the plasma membrane, and exocytosis-related SNARE proteins. The Ca 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
189
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(203 citation statements)
references
References 52 publications
(110 reference statements)
12
189
2
Order By: Relevance
“…Integrative imaging revealed that SARS-CoV-2 infection triggers Golgi fragmentation (Cortese et al, 2020), but the cause and consequence of Golgi fragmentation remain largely elusive. While it was generally believed that mature viral particles are carried by Golgi-derived vesicles to the plasma membrane and secreted to the extracellular space Machamer, 2015, 2019), which is also supported by recent publications (Eymieux et al, 2021), some other reports indicated that SARS-CoV-2 virus may be released by lysosomal exocytosis (Chen et al, 2021;Ghosh et al, 2020). Thus, the route that mediates SARS-CoV-2 trafficking from the Golgi to the extracellular space is still controversial.…”
Section: Introductionmentioning
confidence: 90%
“…Integrative imaging revealed that SARS-CoV-2 infection triggers Golgi fragmentation (Cortese et al, 2020), but the cause and consequence of Golgi fragmentation remain largely elusive. While it was generally believed that mature viral particles are carried by Golgi-derived vesicles to the plasma membrane and secreted to the extracellular space Machamer, 2015, 2019), which is also supported by recent publications (Eymieux et al, 2021), some other reports indicated that SARS-CoV-2 virus may be released by lysosomal exocytosis (Chen et al, 2021;Ghosh et al, 2020). Thus, the route that mediates SARS-CoV-2 trafficking from the Golgi to the extracellular space is still controversial.…”
Section: Introductionmentioning
confidence: 90%
“…It mediates trafficking of lysosomes to plasma membrane and exocytosis-related SNARE vesicle fusion proteins by facilitating lysosomal targeting of the BORC-ARL8b complex. SARS-CoV-2 ORF3a-mediated lysosomal exocytosis requires activity of the Ca 2+ channel TRPML3, as elevated cytosolic Ca 2+ concentration was observed in ORF3a -expressing cells but not in control cells, and TRPML3 knockdown blocked ORF3a-mediated lysosomal exocytosis ( Chen et al, 2021 ). The connection between ORF3a-mediated ion channel activity and viral release has also been observed in SARS-CoV ( Lu et al, 2006 ; Schwarz et al, 2011 ).…”
Section: Orf3a As a Viroporin And Its Role In Viral Pathogenesis And ...mentioning
confidence: 99%
“…In addition, Emodin inhibits ORF3a-mediated ion channel activity and prevents viral release in hCoV-OC43-infected rhabdomyosarcoma RD cells ( Schwarz et al, 2011 ). However, SARS-CoV ORF3a may promote viral release through a different mechanism than SARS-CoV-2 because it does not go through the lysosomal exocytosis pathway ( Chen et al, 2021 ). Interestingly, mutational analysis of SARS-CoV-2 ORF3a shows that residues S171 and W193 are critical for promoting lysosomal exocytosis ( Figure 3C ).…”
Section: Orf3a As a Viroporin And Its Role In Viral Pathogenesis And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lysosomal exocytosis facilitating the clearance of chemotherapeutics accumulated in this organelle is another important component of lysosome-mediated chemotherapy resistance [65]. A recent study has shown that SARS-CoV-2 ORF3a not only inhibits the autophagy flux but also promotes lysosomal exocytosis [66]. This could confer drug resistance to the cancer cells arising in the setting of persistence SARS-CoV-2 ORF3a presence.…”
Section: Implications For Cancer Treatmentmentioning
confidence: 99%